PEMETAAN PERUBAHAN LUASAN HUTAN MANGROVE DENGAN MENGUNAKAN CITRA SATELIT LANDSAT 8 DI PULAU KARAMPUANG KABUPATEN MAMUJU SULAWESI BARAT - Haryanto Asri (Fakultas Perikanan dan Ilmu Kelautan Universitas Muslim Indonesia Makassar, Sulawesi Selatan, 2022)
This study aims to determine the extent of the distribution of mangrove forests in the last 5 years starting from 2017 – 2021. This research was carried out for 1 month, from 1 – 30 April, 2022 on Karampuang Island, Mamuju Regency, West Sulawesi. The method used in this study is the interpretation of Landsat 8 imagery for changes in the area of mangrove cover from 2017 – 2021 and the RGB color composite used is 563. The use of this composite is considered to be able to highlight aspects of the differences between mangrove forests and non-mangrove forests. The results of image interpretation also show a reduction and increase in area from 2017 to 2021. The area of mangrove forests on Karampuang Island fluctuates, namely in 2018 there was an increase in area of 2.16 ha in 2019 there was a reduction in area of 9.02 ha in 2018. In 2020 there will be another reduction of 0.2 ha and in 2021 there will be an addition of 2.59 ha.